2020
DOI: 10.48550/arxiv.2010.04142
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chiral Hinge Magnons in Second-Order Topological Magnon Insulators

Alexander Mook,
Sebastián A. Díaz,
Jelena Klinovaja
et al.

Abstract: When interacting spins in condensed matter order ferromagnetically, their ground state wave function is topologically trivial. Nonetheless, in two dimensions, the ferromagnetic state can support spin excitations with nontrivial topology, an exotic state known as topological magnon insulator (TMI). Here, we theoretically unveil and numerically confirm a novel ferromagnetic state in three dimensions dubbed second-order TMI, whose hallmarks are excitations at its hinges, where facets intersect. Since ferromagneti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 69 publications
(81 reference statements)
0
5
0
Order By: Relevance
“…These techniques will hopefully become more standard among the repertoire of experimentalists for the light that they shed on Berry curvature. Other new and promising directions include the topology of magnetic excitons and bound states (68,142,143), itinerant magnetism, magnon-phonon coupling (144,145), higher order topology (146,147), laser control of magnon topology (148,149) and other out-of-equilibrium phenomena (150).…”
Section: Discussionmentioning
confidence: 99%
“…These techniques will hopefully become more standard among the repertoire of experimentalists for the light that they shed on Berry curvature. Other new and promising directions include the topology of magnetic excitons and bound states (68,142,143), itinerant magnetism, magnon-phonon coupling (144,145), higher order topology (146,147), laser control of magnon topology (148,149) and other out-of-equilibrium phenomena (150).…”
Section: Discussionmentioning
confidence: 99%
“…In the non-collinear phase, it is shown that the simple analogy with electronic states does not apply. We find that the anomalous non-Hermitian terms in the model gap out the two-dimensional surface mode and generate one-dimensional hinge magnon mode [31]. Finally, we propose the symplectic Wilson loop as a novel bulk topological invariant that correctly captures the hinge magnon modes in the higher-order topological magnon phases [28].…”
mentioning
confidence: 84%
“…Magnons, the quanta of spin waves supported by magnetic materials, can also become topological but in reciprocal space [5][6][7][8]. Dictated by the bulk-boundary correspondence, bulk topological magnons can result in robust, unidirectional magnonic currents propagating along the sample edges which have been proposed as information conduits for magnonics [9,10]. So far, the study of topological magnetic textures in real space and topological magnons in reciprocal space have largely developed as independent fields.…”
Section: Introductionmentioning
confidence: 99%